Cardiovagal Baroreflex Hysteresis Using Ellipses in Response to Postural Changes - Dabiri, Babak; Brito, Joana; Kaniusas, Eugenijus (Frontiers in Neuroscience, 2021)
Cardiovagal branch of baroreflex is of high clinical relevance when detecting disturbances of the autonomic nervous system. The hysteresis of baroreflex is assessed using provoked and spontaneous changes in blood pressure. We propose a novel ellipse analysis to characterize hysteresis of the spontaneous respiration-related cardiovagal baroreflex for orthostatic test. Up and down sequences of pressure changes as well as the working point of baroreflex are considered. EuroBaVar data set for supine and standing was employed to extract heart beat intervals and blood pressure values. The latter values formed polygons into which bivariate normal distribution was fitted with its properties determining proposed ellipses of baroreflex. More than 80% of ellipses was formed out of non-overlapping and delayed up and down sequences highlighting baroreflex hysteresis. In supine, the ellipses are more elongated (by about 46%) and steeper (by about 4.3° as median) than in standing, indicating larger heart intervals variability (70.7ms versus 47.9ms) and smaller blood pressure variability (5.8mmHg versus 8.9mmHg) in supine. The ellipses have shown a higher baroreflex sensitivity for supine (15.7ms/mmHg as median) than standing (7ms/mmHg). The center of the ellipse moves from supine to standing which describes the overall sigmoid shape of the baroreflex with the moving working point. In contrast to regression analysis, the proposed method considers gain and set-point changes during respiration, offers instructive insights into the resulting hysteresis of the spontaneous cardiovagal baroreflex with respiration as stimuli, and provides a new tool for its future analysis.